Pengukuran Kepuasan Kerja Karyawan APLP & A PT Semen Padang (PT X) - Shelly Nolandari; Henmaidi; Alizar Hasan (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
Thoughts on employee satisfaction arise because the company believes its employees have a high level of satisfaction will result in a better level of productivity, work more accurate, the fewer the number of absences and higher loyalty than employees with low satisfaction levels.Company's with good productivity will grow and increase revenue. PT Semen Padang has several subsidiaries and affiliates like PT X. PT X will measure employee satisfaction with the company's expectations are always making changes that sustainable about employee satisfaction because companies believe that employee satisfaction level of its high yield levels better productivity, work more accurate, the number of absences are fewer and loyalty higher than employees with low satisfaction levels. Companies with good productivity will experience growth as indicated by the increase in revenue, in line with the increase in the welfare of the employees. PT Semen Padang has several subsidiaries and affiliates PT X. PT Xwill measure employee satisfaction with the Company's expectations.